Analysis of a high pressure diesel spray at high pressure and temperature environment conditions - Kidoguchi, Yoshiyuki; Nada, Yuzuru; Yano, Takayuki; Nakagiri, Misato (Japan Society of Mechanical Engineers, 2013)
This paper illustrates the results of an experimental characterization of a high pressure diesel spray injected by a common rail (CR) injection system both under non-evaporative and evaporative conditions. Tests have been made injecting the fuel with a single hole injector having a diameter of 0.18 mm with L/D=5.56. The fuel has been sprayed at 60, 90 and 120 MPa, with an ambient pressure ranging between 1.2 to 5.0 MPa. The spray evolution has been investigated, by the Mie scattering technique, illuminating the fuel jet and acquiring single shot images by a CCD camera. Tests under non-evaporative conditions have been carried out in an optically accessible high pressure vessel filled with inert gas (N2) at diesel-like density conditions. The instantaneous fuel injection rate, obtained with a time resolution of 10 microseconds, has been also evaluated by an AVL Fuel Meter working on the Bosch Tube principle. Tests for the evaporative conditions have been conducted on a crank-case scavenged single cylinder 2-stroke direct injection Diesel engine at the rotational speed of 500 rpm. The engine provides a wide optical access and the gas velocity within the combustion chamber is low enough to assume that the fuel is injected under quiescent conditions as those reproduced for the experiments under high density gas chamber. Spray penetration and cone angle have been estimated at the same operative conditions as for the non-evaporative ones. Results have showed that the tip penetration, obtained by digital post-processing of the spray image sequence, increases with the injection time under non-evaporative conditions whereas, under evaporative conditions, it reaches a maximum early during the injection and remains constant or slightly decreases at later time up to the start of combustion. The cone angle, estimated under evaporative conditions, has given a decreasing profile along the injection interval. Applying the jet theory to a simplified model of fuel spray, the evaporated fuel mass has been estimated at the same gas density as that under non evaporative tests.